The magic of the Mezuzah in rabbinic literature - Jansson, Eva-Maria (Nordisk judaistik/Scandinavian Jewish Studies, 1994)
The notion that the mezuzah – the capsule containing a parchment strip on which is written Deut 6:4-9 and 11:13-21 and which is attached to the doorposts of a Jewish home – is protective has been explained in different ways. Two different developments have been suggested: either the mezuzah was originally an amulet, which the rabbis sought to theologize, or it was a religious object which fell victim to popular superstitious notions. In this paper, where the study is delimited to the Talmudic and some Geonic material, I intend to propose another explanation to the origin and development of the idea of its protectiveness. The origin of the mezuzah as an object is obscure. The oldest references we have to it, e.g. in the Mishnah and the Tosefta, presuppose that it is an object on par with other religious objects, and that the affixing of the mezuzah is a mitzvah. To conclude that traditions found in later texts, regarding it as an amulet, are pre-Rabbinic and preserved unaffected by the Rabbinic mediation, is problematic. Discerning a popular influence, that is, a popular strata in the Talmudin, the She’iltot, Sefer Halakhot Gedolot and the Hekhalot literature, opposed to the views of the Rabbinic elite, is also difficult.